The Medicinal Potential of Mesenchymal Stem/Stromal Cells in Immuno- and Cancer Therapy - Mehdi Najar; Hassan Fahmi; Makram Merimi (Biomolecules, 2023)
Cancer is a highly lethal disease that causes millions of deaths worldwide, thus representing a major public health challenge [...]